SDGs Challenges and Expectations: Qualitative Study On The Role Of Stakeholders In Overcoming Stunting - Nainggolan, Wiwiek Elsada; Khoiriyah, Fitri; Hidayati, Yusmalia; Lubis, Dita Anggriani; Agustia, Dilma'aarij Riski; Br Gultom, Ria Fazelita (LPPM Universitas PGRI Sumatera Barat, 2024)
Stunting is a serious public health problem and is directly related to the Sustainable Development Goals (SDGs), especially in eliminating hunger and malnutrition and achieving food security. Stunting occurs when children experience chronic malnutrition in the early phases of their growth, which impacts their physical and cognitive development. Handling stunting requires integrated and collaborative efforts from various stakeholders to address its main causes and achieve national and global targets. This research aims to analyze the role of stakeholders in overcoming stunting. The research design uses a qualitative descriptive design. The informants in the research were 7 people (representatives from the Medan City Health Service, Sunggal Community Health Center, Sunggal District, North Sumatra BKKBN). Sampling used purposive sampling technique in accordance with the inclusion criteria. The research was conducted at Satya Terra Bhinneka University using Focus Group Discussion (FGD) guidelines. Analysis of FGD data using interactive analysis techniques. The research results reveal the phenomenon of stunting and SDGs from the perspective of informants as stakeholders. Stunting has a long-term impact on children's growth and development, and can affect future health and productivity. It is hoped that the results of this research can be used by the Government and all related parties to achieve the targets that have been set and work together to significantly reduce the prevalence of stunting.